2023
DOI: 10.3390/molecules28020518
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound- and Microwave-Assisted Extraction for the Determination of Phenolic Compounds in Peach Byproducts Using Experimental Design and Liquid Chromatography–Tandem Mass Spectrometry

Abstract: The conversion of plant byproducts, which are phenolic-rich substrates, to valuable co-products by implementing non-conventional extraction techniques is the need of the hour. In the current study, ultrasound- (UAE) and microwave-assisted extraction (MAE) were applied for the recovery of polyphenols from peach byproducts. Two-level screening and Box–Behnken design were adopted to optimize extraction efficiency in terms of total phenolic content (TPC). Methanol:water 4:1% v/v was the extraction solvent. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Moreover, numerous studies have demonstrated that the solvent concentration, solvent-to-sample, temperature, and pressure rate parameters affect the extraction yield [ 32 , 33 , 34 ]. Our results are in agreement with those of Bansodet al [ 35 ] and Tsiaka et al, [ 36 ], who reported that the optimization parameters influence the extraction of both bioactive compounds and antioxidant activities. In the current study, special interest has been given to microwave-assisted extraction (MAE) due to its positive impact on the extraction of bioactive compounds, i.e., higher product yields and shorter extraction times [ 37 , 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, numerous studies have demonstrated that the solvent concentration, solvent-to-sample, temperature, and pressure rate parameters affect the extraction yield [ 32 , 33 , 34 ]. Our results are in agreement with those of Bansodet al [ 35 ] and Tsiaka et al, [ 36 ], who reported that the optimization parameters influence the extraction of both bioactive compounds and antioxidant activities. In the current study, special interest has been given to microwave-assisted extraction (MAE) due to its positive impact on the extraction of bioactive compounds, i.e., higher product yields and shorter extraction times [ 37 , 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Mokrani and Madani [131] worked on the extraction of phenolic compounds from whole peach fruit, investigating the impact of various parameters, such as time, temperature, solvent type, acetone concentration, and solvent acidity, on the extraction yield. They determined that the optimal extraction conditions entailed using 60% acetone without acidification, with an extraction duration of 180 min at a temperature of 25 • C. In a different approach, Tsiaka et al [132] focused on the extraction of phenolic components from peach skin and pomace using ultrasound-and microwave-assisted techniques. The ultrasound-assisted extraction was optimized at an extraction time of 15 min, a pulse duration/pulse interval ratio of 8/5, and a solvent/solid ratio of 35/1 mL/g.…”
Section: Valorization Of Peach Pomacementioning
confidence: 99%
“…Several research groups have been interested in the extraction of pectin from food waste and byproducts using microwave-assisted extraction [27]. This method has been also employed to extract polyphenols from eucalyptus bark [28], peach byproducts [29], and cellulose from almond shell waste [24]. Solid-liquid extraction is a method that is based on transferring the desired compounds from the solid phase to the liquid-extractant phase, usually by employing organic solvents [30].…”
Section: Introductionmentioning
confidence: 99%